Cosmological tensions in H0 and S8: current overview - Silva, Emanuelly; Sabogal, Miguel; Nunes, Rafael (Cadernos de Astronomia, 2026)
The standard cosmological model has provided, for several decades, a consistent description of a wide range of cosmological and astrophysical observations. Despite this success, persistent discrepancies in the determination of fundamental parameters, in particular the Hubble constant (H0) and the amplitude of structure growth, commonly parametrized by S8, reveal significant tensions between probes of the early and late universe, with varying levels of statistical significance. These tensions may be partially associated with systematic uncertainties that are not yet fully understood, but they also motivate the investigation of extensions of ΛCDM, including modifications to dark energy, the dark sector, and gravity on large scales. In this didactic review, we present an overview of the main observations currently involved in these discrepancies, discuss their potential observational biases, and synthesize the most relevant theoretical scenarios, highlighting the prospects offered by current-generation cosmological surveys.
Keywords: cosmological parameters; Hubble tension (H0); S8 tension; cosmological anomalies and tensions in ΛCDM